PEMANFAATAN MEDIA PEMBELAJARAN AUDIOVISUAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI PADA ANAK TUNA RUNGU SMPLB DI SLB NEGERI 1 TABANAN - Ni Wayan Astini; I Ketut Suda; I Wayan Sukadana (WIDYANATYA, 2022)
Extraordinary Education or Extraordinary School (SLB) is an education for learners who have a level of difficulty in following the learning process due to physical, emotional, mental social disorders, but have the potential for special intelligence and talent. The use of learning media also has an important role in thelearning process both in public schools and in extraordinary schools. The use of learning media also has an important role in the learning process both in public schools and in extraordinary schools. Like SLB Negeri 1 Tabanan has utilized audio visual learning, especially in deaf children of SMPLB at SLB Negeri 1 Tabanan. This research was carried out to answer the problem about What is the process of utilizing Audio Visual learning media in the learning of Hindu and BudiPekerti education in deaf children of SMPLB at SLB Negeri 1 Tabanan. The purpose of this study is to find out the use also the implication of audio visual learning mediain the learning of Hindu and Budi Pekerti Religious Education in deaf children at SLB Negeri 1 Tabanan. This research is in the form of qualitative design. Data is collected using data collection techniques as a first step in the completion of scientific works, namely Observation Techniques, Interview Techniques, and Documentation Study Techniques. After the data is collected, it is then processed using qualitative descriptive data analysis techniques. Based on the analysis above, the results of this study can be described as follows:12). In the learning processwith audio visual media, in general there are several steps in the use of audio visual media that must be done, namely: (a) Preparation, (b) Preparing for class, (c) Presentation, (d) Advanced activities. Although in this learning is useful does not mean there are no obstacles. As for some of the obstacles faced by Hindu teachersin the learning process with audio visual media in deaf children, which consists ofseveral factors, namely, student factors, family factors, teacher factors, and schoolfactors.2) 3). the use of audio visual media using video provides changes or benefits for students and teachers in learning Hindu and Budi Pekerti Religious Educationin deaf children of SMPLB at SLB Negeri 1 Tabanan. ABSTRAK Pendidikan Luar Biasa atau Sekolah Luar Biasa (SLB) merupakan pendidikan bagi peserta didik yang memiliki tingkat kesulitan dalam mengikuti proses pembelajaran karena kelainan fisik, emosional, mental sosial, tetapi memiliki potensi kecerdasan dan bakat istimewa. Penggunaan media pembelajaranjuga memiliki peranan penting dalam proses pembelajaran baik disekolah umum maupun di sekolah luar biasa. Seperti halnya SLB Negeri 1 Tabanan telah memanfaatkan pembelajaran audio visual khususnya pada anak tunarungu SMPLBdi SLB Negeri 1 Tabanan. Penelitian ini dilaksanakan untuk menjawabpermasalahan tentang Bagaimana proses serta implikasi dari pemanfaatan media pembelajaran Audio Visual dalam pembelajaran pendidikan Agama Hindu dan Budi Pekerti pada anak tunarungu SMPLB di SLB Negeri 1 Tabanan. Penelitian ini berbentuk rancangan kualitatif. Data dikumpulkan dengan menggunakan teknik pengumpulan data sebagai langkah awal dalam penusunan karya ilmiah, yaitu Teknik Observasi, Teknik Wawancara, dan Teknik Studi Dokumentasi. Setelah data terkumpul kemudian diolah dengan menggunakan teknik analisis data deskriptif kualitatif. Berdasarkan analisis diatas, hasil penelitian ini dapat diuraikan sebagaiberikut: 1) Dalam proses pembelajaran dengan media audio visual, secara umum ada beberapa langkah-langkah dalam penggunaan media audiovisual yang harus dilakukan, yaitu: (a) Persiapan, (b) Mempersiapkan kelas, (c) Penyajian, (d) Aktifitas lanjutan. Meskipun dalam pembelajaran ini bermanfaat bukan berarti tidak ada kendala. Adapun beberapa kendala yang dihadapi guru Agama Hindu dalam proses pembelajaran dengan media audio visual pada anak. 2). pemanfaatan media audio visual dengan menggunakan video memberikan perubahan atau manfaat bagi peserta didik maupun guru dalam pembelajaran Pendidikan Agama Hindu dan Budi Pekerti padaanak tunarungu SMPLB di SLB Negeri 1 Tabanan. tunarungu, yang terdiri dari beberapa faktor yaitu, faktor peserta didik, faktor keluarga, faktor guru, dan faktor sekolah.